Reconstruction of National Sports System Policy to Improve Sports Achievement - A. , Lilik Sudarwati; Jarudin (International Journal of Psychosocial Rehabilitation, 2020)
The development of the sport is an integral part of national development, especially human resource development. This leads, among others, to 1) improvement of people’s physical health; 2) improvement of the mental and spiritual health of the people; 3) national character and personality building; 4) discipline and sportiveness; and 5) improvement in achievement that arouses a sense of national pride. The study employed a paradigm model of normative legal approach. The primary data sources are interviews conducted with policy-making officials/personnel and sport stakeholders such as the People’s Representative Council, KONI, Provincial KONI, KOI, EB/CB, Chief of the National Sport Governing Body, and national sport law experts. The secondary data sources are primary, secondary, and tertiary legal sources. The collected data are analyzed qualitatively, and the conclusion is based on inductive reasoning. The results show that Law No. 3 of 2005 on NSS has not been optimally implemented in terms of the structure of the law, the substance of the law, legal culture, communication, and resources. Therefore, it is necessary to develop a new holistic and continuous concept, or a Triple Helix concept of human resource security that combines health, education, and sports.